Amir Temur's State and It’s Department - Anvar , Allamuratov (Indonesian Journal Publisher, 2024)
This study explores the governance system and administrative reforms implemented by Amir Timur, drawing from historical texts that highlight his consolidation of power and state-building efforts. Initially adopting Mongol administrative structures, Timur gradually reformed these systems to create a highly centralised state apparatus. Amir Timur’s state-building initiatives merged traditional Central Asian governance models with the Mongol administrative legacy. Initially adopting the Mongol structure, Timur later implemented extensive reforms to centralise authority and strengthen his empire. He established a complex administrative system divided into seven ministries, each responsible for functions such as taxation, trade, and justice. Timur's governance was deeply influenced by Islamic principles, emphasising sharia law and council deliberations to ensure stability. The